Structural rearrangements in the mitochondrial genome of Drosophila melanogaster induced by elevated levels of the replicative DNA helicase. Issue 6 (8th February 2018) - Ciesielski, Grzegorz L; Nadalutti, Cristina A; Oliveira, Marcos T; Jacobs, Howard T; Griffith, Jack D; Kaguni, Laurie S
Abstract: Pathological conditions impairing functions of mitochondria often lead to compensatory upregulation of the mitochondrial DNA (mtDNA) replisome machinery, and the replicative DNA helicase appears to be a key factor in regulating mtDNA copy number. Moreover, mtDNA helicase mutations have been associated with structural rearrangements of the mitochondrial genome. To evaluate the effects of elevated levels of the mtDNA helicase on the integrity and replication of the mitochondrial genome, we overexpressed the helicase in Drosophila melanogaster Schneider cells and analyzed the mtDNA by two-dimensional neutral agarose gel electrophoresis and electron microscopy. We found that elevation of mtDNA helicase levels increases the quantity of replication intermediates and alleviates pausing at the replication slow zones. Though we did not observe a concomitant alteration in mtDNA copy number, we observed deletions specific to the segment of repeated elements in the immediate vicinity of the origin of replication, and an accumulation of species characteristic of replication fork stalling. We also found elevated levels of RNA that are retained in the replication intermediates. Together, our results suggest that upregulation of mtDNA helicase promotes the process of mtDNA replication but also results in genome destabilization.